Synthesis and thermal study of polymers from soybean, sunflower, and grape seed maleinated oil - Alarcon, Rafael Turra [UNESP]; Vinícius de Almeida, Marcos [UNESP]; Rinaldo, Daniel [UNESP]; Bannach, Gilbert [UNESP] (Wiley, 2017)
This paper presents the synthesis of some polymers from maleinated vegetable oils (soybean, sunflower, and grape seed) and glycerol. First, all the vegetable oils were previously maleinated with maleic anhydride, then, the maleinated oils were esterified with glycerol to obtain the polymers; the synthetic route is simple and not use organic solvents, the results indicate that the synthesis was effortless and use inexpensive reagents, such as vegetable oils, maleic anhydride, and glycerol. These polymers could be applied in the area of adhesives and waterproofing materials. The results obtained by TGA-DTA and DSC data showed that these polymers had different thermal behaviors, which is related to the different quantity of unsaturated fatty acids in each oil structure. Finally, the FTIR and 1H-NMR analysis help to clarify the polymers structure and the reaction sites: hence, it was possible to propose a reaction mechanism and the structure. Practical applications: The polymer synthesis of each vegetable oil was similar in time and process; however, the final product presented different physical characteristics. The results obtained by TGA-DTA and DSC data showed that these polymers had different thermal behaviors, which is related by different quantity of unsaturated fatty acids in each oil structure. Finally, the FTIR and 1H-NMR analysis help to clarify the polymers structure and the reaction sites: hence, it was possible propose a reaction mechanism and the structure. The results indicate that the synthesis was effortless and use inexpensive reagents, such as vegetable oils, maleic anhydride, and glycerol. These polymers could be applied in the area of ​​adhesives and waterproofing materials. In this work synthesis of polymers from maleinated oils (soybean, sunflower, and grape-seed) is shown. Possible structure is made by FTIR and 1H-NMR analysis as well as its thermal characterization by TGA-DTA and DSC.
Keywords: Glycerol; Grape seed oil; Maleinated vegetable oils; Polymers; Thermal studies; Vegetable oil-based